Genetic Characterization of Procambarus clarkii Cultured in Sichuan Province Based on Microsatellite Markers - Changwen Deng; Qingqing Liao; Yingying Ren; Wuyuntana Shao; Yunkun Li; Shiyong Yang; Xiaogang Du; Jiayun Wu (Fishes, 2024)
The Procambarus clarkii production sector in Sichuan Province, China, is experiencing rapid growth. However, the industry faces significant challenges, including on-farm breeding and the widespread “Catch Big, Keep Small” farming practice, which have led to substantial genetic degradation within P. clarkii populations. Moreover, the uncertainty surrounding the origins of breeding stocks poses an additional obstacle to the local selection and cultivation of high-quality juvenile P. clarkii. With the objective of inferring the genetic lineage of cultivated P. clarkii in Sichuan, twelve microsatellite loci were employed to investigate the genetic characters of six P. clarkii populations from Sichuan and two from Hubei Province, China. The results revealed that the Sichuan populations exhibited higher levels of heterozygosity (Ho = 0.549~0.699, He = 0.547~0.607) and genetic diversity than the Hubei populations (Na = 4.00~5.250, PIC = 0.467~0.535). Notably, the DY population located in northeastern Sichuan showed the highest heterozygosity (Ho = 0.699, He = 0.607) and genetic diversity (Na = 5.250, PIC = 0.535) among the eight populations. Population structure, principal coordinate analysis and clustering analysis illuminated a close genetic relationship between the Qionglai population in Sichuan and the Jianli population in Hubei. Additionally, the remaining five Sichuan populations (Luxian, Nanxi, Xingwen, Neijiang and Daying) exhibited strong genetic affinity with the QianJiang population in Hubei, and particularly high genetic exchange may have occurred between Daying and Qianjiang (Fst = 0.001, Nm = 217.141). These results suggest that the primary cultivated P. clarkii populations in Sichuan likely originated from Qianjiang and Jianli counties in Hubei, with Qianjiang contributing a more substantial proportion. The genetic diversity of Sichuan populations was higher than those of some other Chinese P. clarkii farming provinces and even some native populations. Specifically, the Daying population emerges as a potential breeding germplasm source for crayfish in Sichuan. In contrast, the Qionglai population exhibits relatively low genetic diversity, highlighting the need for strategic enhancement through interactions with other populations to promote diversity and resilience. Furthermore, fostering genetic exchange among locally cultivated populations within the southern Sichuan basin is strategic to elevate the quality of P. clarkii germplasm resources.